Electronic health records for dummies - Williams, Trenor; Samarth, Anita (--For dummies., 2018)
The straight scoop on choosing and implementing an electronic health records (EHR) system. Doctors, nurses, and hospital and clinic administrators are interested in learning the best ways to implement and use an electronic health records system so they can be shared across different health-care settings via a network-connected information system. This helpful, plain-English guide provides need-to-know information on how to choose the right system, assure patients of the security of their records, and implement an EHR in such a way that it causes minimal disruption to the daily demands of a hospital or clinic. Offers a plain-English guide to the many electronic health records (EHR) systems from which to chooseAuthors are a duo of EHR experts who provide clear, easy-to-understand information on how to choose the right EHR system and implement it effectivelyAddresses the benefits of implementing an EHR system so critical information (such as medication, allergies, medical history, lab results, radiology images, etc.) can be shared across different health-care settingsDiscusses ways to talk to patients about the security of their electronic health recordsElectronic Health Records for Dummies walks you through all the necessary steps to successfully choose the right EHR system, keep it current, and use it effectively.